KAJIAN RETORIKA KIAS SINDIR DALAM BAHASA MELAYU BENGKULU - Andra, Vebi (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2015)
The aim of this research is to study satire simile rhetoric in Bengkulunese Malay language, either in every sort or its pragmatic function. The use method was the descriptive method. The data colletion technique has been done with observation study and interview. Whereas the data analysis was based on the technique of transcribing, identifying, classifying, and concluding. The research object was satire simile rhetoric in Bengkulunese Malay language. The result of the research show, that the sort of satire simile rhetoric in Bengkulunese Malay language was divided into aphorism and parable. While the pragmatic function of satire simile rhetoric in Bengkulunese Malay language, based on its function could be classified into satire on deed (attitude) was done by a person or a group of persons and advice (teaching guidance) by meant a person or a group of persons could live well.